تغير مسارات نهر دجلة القديم عبر التاريخ بين محافظتي واسط وذي قار - علي، سحر عبدالرضا; العجيلي، عبدالله صبار عبود; العبدان، رحيم حميد عبد ثامر (جامعة بغداد - كلية الآداب, 2021)
يقع مجرى نهر دجلة القديم بين ثلاث محافظات (واسط – ميسان- ذي قار) إذ يحيط بها من الشرق والشمال نهر دجلة الحالي، ومن الغرب نهر الغراف ومن الجنوب نهر الفرات، وتبلغ مساحة منطقة الدراسة (16473.2كم2)، وامتاز نهر دجلة في منطقة الدراسة المحددة بعدم استقراره في مجراه عبر الزمن، منذ البلايستوسين وحتى العهد الساساني. وكان أخر تغير له في أواخر العهد الساساني، حيث انتقل المجرى من مجراه الأصلي الذي كان يجري فيه عبر الكوت إلى الناصرية إلى مجراه الحالي من الكوت إلى العمارة.
The course of the old Tigris River is located between three governorates (Wasit - Maysan - Dhi Qar) as it is surrounded from the east and north by the current Tigris River, from the west by the Gharraf River and from the south by the Euphrates River. The area of the study area is (16473.2 km2). Tigris in the selected study area was characterized by its instability in its course through time, from the Pleistocene to the Sassanid era. Its last change was at the end of the Sassanid era, when the stream moved from its original course in which it was running through Kut to Nassiriyah to its current course from Kut to Amara.
Keywords: الجغرافية التاريخية -- نهر دجلة -- المجرى المائي -- المسارات المائية